2018
DOI: 10.3892/ijmm.2018.3829
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lncRNA NEAT1 suppresses the inflammatory response in IBD by modulating the intestinal epithelial barrier and by exosome-mediated polarization of macrophages

Abstract: Inflammatory bowel disease (IBD) is a multifactorial inflammatory disease, and increasing evidence has demonstrated that the mechanism of the pathogenesis of IBD is associated with intestinal epithelial barrier injury. Long non‑coding RNAs (lncRNAs) are a class of transcripts >200 nucleotides in length with limited protein‑coding capability. Nuclear paraspeckle assembly transcript 1 (NEAT1) is a recently identified nuclear‑restricted lncRNA, which localizes in subnuclear structures, termed paraspeckles, and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 41 publications
(42 reference statements)
0
82
0
Order By: Relevance
“…Intriguingly, NEAT1 has been recently identified as a novel inflammatory regulator in human lupus [24]. Additionally, blocking NEAT1 expression may treat inflammatory bowel disease by suppressing inflammatory progression [25]. The anti-inflammatory efficacy of NEAT1 also has been demonstrated in mice with traumatic brain injury [12].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, NEAT1 has been recently identified as a novel inflammatory regulator in human lupus [24]. Additionally, blocking NEAT1 expression may treat inflammatory bowel disease by suppressing inflammatory progression [25]. The anti-inflammatory efficacy of NEAT1 also has been demonstrated in mice with traumatic brain injury [12].…”
Section: Discussionmentioning
confidence: 99%
“…39 In UC mouse blood lncRNAs Neat1 and Panct2 also showed to be SDE in disease. Neat1 is shown to be pro-inflammatory and its inhibition suppresses the inflammatory response in IBD, 40 whereas little is known about Panct2. Moreover, numerous SDE lncRNAs not reported before in UC mouse including top three upregulated 9130221F21Rik, E230034D01Rik, 1200007C13Rik in colon and Gm7457, Gm37800, Gm32486 in blood and many more up-and downregulated new lncRNAs were identified in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that NEAT1 participates in several biological events, such as proliferation, polarization invasion and metastasis [31][32][33]. However, the function of NEAT1 in EC dysfunction remains unknown.…”
Section: Discussionmentioning
confidence: 99%